Bukit Bunuh Lenggong Malaysia A new Evidence of Late Pleistocene Culture in Malaysia and Southeast Asia. - Saidin, Mohd Mokhtar (2004)
A new Palaeolithic site- Bukit Bunuh- discovered tn 2002 has thrown light on Malaysia's Palaeolithic, and findings from this site will have to be considered in the interpretation of other Palaeolithic sites in Southeast Asia.